Optical properties of some [(As2S3)0.5:(As2Se3)0.5]1-x:Snx chalcogenide glasses - Iaseniuc, Oxana (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2012)
The transmission spectra of bulk and thin films of [(As2S3)0.5:( As2Se3)0.5]1-x:Snx in the visible and near infrared (IR) regions were investigated. The doping of As2(S, Se)3 chalcogenide glass with tin impurities essentially reduces the absorption bands of S-H (Se-H) and H2O located at ν = 5190 cm-1 and ν = 3617 cm-1, respectively. The amorphous [(As2S3)0.5:(As2Se3)0.5]1-x:Snx thin films exhibit photoinduced effects under the light irradiation with photon energy above the optical band gap (hν≥Eg), which makes them promising materials for registration of optical and holographic information. The modification of optical parameters (optical band gap Eg, absorption coefficient α, refractive index n) under light irradiation and heat treatment of amorphous thin films with different amounts of Sn was studied. The relaxation of photodarkening effect in amorphous [(As2S3)0.5:(As2Se3)0.5]1-x:Snx thin films, which is described by the stretch exponential function T(t)/T(0) = A0 Aexp[-(t-t0)/τ](1-α), was also investigated.